2013
DOI: 10.5194/acp-13-4593-2013
|View full text |Cite
|
Sign up to set email alerts
|

Laser filament-induced aerosol formation

Abstract: Using the aerosol and cloud simulation chamber AIDA, we investigated the laser filament induced particle formation in ambient air, humid synthetic air, humid nitrogen, argon–oxygen mixture, and pure argon in order to simulate the particle formation under realistic atmospheric conditions as well as to investigate the influence of typical gas-phase atmospheric constituents on the particle formation. Terawatt laser plasma filaments generated new particles in the size range 3 to 130 nm with particle production rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Clouds were created by adiabatic expansion in atmospheres consisting of synthetic air with cloud condensation nuclei (CCN) either produced photochemically by the laser filament action (21) or introduced before the expansion as well-defined mineral dust and sulfuric acid particles (for details, see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Clouds were created by adiabatic expansion in atmospheres consisting of synthetic air with cloud condensation nuclei (CCN) either produced photochemically by the laser filament action (21) or introduced before the expansion as well-defined mineral dust and sulfuric acid particles (for details, see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…As we recently showed that the effect of the laser mainly consists in enhancing natural phenomena, as opposed to opening fully new condensation pathways [10], the local yield in laser--induced particles provides a relevant probe of the natural potential of the probed air mass to produce condensation under appropriate conditions. As such, it can be considered as bearing a composite information on all physical and chemical parameters influencing photochemical new particle formation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we propose to use this signal to extract physical or chemical parameters (T, RH, pre--existing nanoparticles, volatile organic compound (VOC) concentration…) that influence laser--induced condensation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…14 Oxidized volatile organic compounds (VOCs), which are known to significantly enhance water vapor condensation in the atmosphere, 20 were more recently shown to offer an alternative pathway in the laser-induced condensation process. 16 The nanoparticle production by NIR laser pulses up to the 100 TW level scales non-linearly with the incident power and energy. 19 This non-linearity is a consequence of the strong contribution from the NIR photon bath, i.e., the nonfilamenting part of the beam.…”
Section: 18mentioning
confidence: 99%
“…10 The resulting plasma wake modifies the physico-chemical properties of the air, allowing the formation of liquid [11][12][13] or solid 14,15 aerosol particles in sub-saturated air, in both the atmosphere 12 and the laboratory. 16 This phenomenon is promising as a technique for analyzing and possibly modifying both microscopic and macroscopic cloud behaviors, 15 in particular, if the type, number, and size distribution of droplets can be controlled.…”
mentioning
confidence: 99%